Use of Microbiological Methods in Postmortem Interval Estimation - Yıldırım, Mahmut Şerif; Sevinç, Sinan; Akçan, Ramazan; Odabaşı, Aysun Balseven; Tümer, Ali Rıza (The Bulletin of Legal Medicine, 2015)
Postmortem interval estimation is one of the most important issues of postmortem investigation. Although there are several methods utilized in postmortem interval estimation, most of these are far from providing accurate interval. Thus, there is a strong need for novel methods or improvement of conventional ones. Among these, the place, role and efficiency of microbiological methods in postmortem interval estimation are still controversial. This paper aims to attract attention to the use of microbiology in postmortem interval estimation and discuss its role in the light of the related literature.Keywords: Microbiology, Postmortem interval, Forensic pathology